Biotransport of marine-derived trace elements to a coastal ecosystem in the Canadian High Arctic - Brimble, Samantha (University of Ottawa (Canada), 2009)
Seabirds are an important link between their marine feeding areas and their terrestrial breeding environments, transporting both marine-derived nutrients and contaminants to land via their excreta, feathers and carcasses. The importance of seabird-derived nutrients is particularly apparent in nutrient poor regions like the Canadian High Arctic, where biological oases form in the area surrounding a colony. While providing the nutrient subsidies that shape the terrestrial ecosystem of many Arctic sites, seabirds may focus contaminants into their nesting sites at potentially toxic levels. Here, we investigated the impact of a large northern fulmar (Fulmarus glacialis) colony on nearby ponds spanning a broad gradient of seabird influence at Cape Vera, Devon Island. Nutrient concentrations were significantly higher in ponds receiving guano than in reference ponds. The ponds closest to the cliffs, and thus receiving the highest seabird subsidies, were the most contaminated, and in some cases exceeded Canadian Sediment Quality Guidelines for the Protection of Aquatic Life for As, Cd and Zn. This study demonstrates that seabirds can transport contaminants bioaccumulated from the ocean and funnel them into receptor sites to potentially toxic levels thousands of kilometers from industrial centers.
Keywords: Biology, Ecology.; Biology, Oceanography.